An entropy based approach to 5S maturity. (2021) - Ranjith Kumar, Rajan; Ganesh, L.S.; Rajendran, Chandrasekharan
Abstract: Research literature points to 5S, a simple yet powerful method of initiating quality in workspaces, as one of the foundations of other quality practices such as Lean and TPM. This paper presents the multi-dimensional challenges in 5S implementation, the need for a quantitative measure of 5S realization, a justification for and a suggestion of a 5S maturity model. The paper presents the conceptual foundations of entropy to measure disorder in an enclosed space, which provides the basis for measuring 5S practice maturity. The paper contributes to the existing body of knowledge by proposing a novel method founded on the concept of entropy to map the maturity of 5S implementation.